EVALUATION OF MUDSTONE FORMATIΟNS AND THEIR SUITABILITY FOR CERAMICS PRODUCTION - Καστρίνάκη Α.; Τσιραμπίδης Α.; Μιχαηλίδης Κ.; Τρώντσιος Γ. (Bulletin of the Geological Society of Greece, 2004)
Mudstone formations samples from the Thessaloniki and Chalkidiki prefectures are investigated, in respect to their suitability as raw materials for the ceramic industry. In particular, the investigation concerned the determination of the mineralogical and chemical composition of the studied sample. Quartz and feldspars are the major mineralogical constituents, whereas micas, clay minerals and carbonates were detected in various amounts, follow. The samples are evaluated, concerning their suitability for ceramics production, namely majiolica, cottoforte, gre and bricks, on the basis of their chemical composition and in accordance to Si02-Al203-Fe203t, Si02 (Fe203t+K20+Na20+CaO+MgO)-(AI203+Ti02) and Fe203t-(CaO+MgO)-(K20+Na20) triangular diagrams. The general conclusion is that, most of the studied materials are unsuitable for high quality ceramics products. By contrast, some of them could be tested for the production of bricks and roofing tiles.